Activation of defense response in som plant against leaf blight following application of bioinoculants - USHA CHAKRABORTY, DHRUVA KUMAR JHA; JINTU RABHA, BISHWANATH CHAKRABORTY*, AMRITA ACHARYA (Indian Phytopathology, 2016)
Eight different morphotypes (S1-S8) of Persea bombycina, locally known as som plant, were grown in pots under nursery condition where the soil was supplemented with varieties of bio-inoculants like Plant Growth Promoting Rhizobacteria (PGPR), Arbuscular Mycorrhizal Fungi (AMF) and Plant Growth Promoting Fungi (PGPF) alone or in combinations. Among these eight morphotypes, S5 and S6 showed improved growth. These two morphotypes were further transplanted in field where the soil was amended with talc-based formulation of Bacillus altitudinus, wheat bran based formulation of Trichoderma asperellum and mass multiplied spores of AMF. Enhancement of growth was evidenced in treated plants by increase in plant height (cm), total number of branches and number of leaves. Following the application of these bioformulations, soil phosphate content decreased and root phosphate increased in case of treated plants. Increase in chlorophyll content as well as total soluble protein content of the leaves of treated plants was also recorded. Significant increase in phenolics (total as well as orthophenol content), and in defense enzymes such as chitinase (CHT), Î²-1,3 glucanase (GLU), phenylalanine ammonia-lyase (PAL), and peroxidase (POX) were also observed in both roots and leaves following the application of the bioformulation. HPLC analysis for detecting changes in leaf phenolic content revealed production of a new phenolic acid after treatment with the bioinoculants. The leaves of treated and untreated plants (S5 and S6) were inoculated with spores of Colletotrichum gloeosporioides, the causal agent of leaf blight disease of the host plant. Assay of major defense enzymes PAL, POX, CHT and GLU as well as total phenol content after every 24 hr of inoculation for 72hr showed that the level of these enzymes were more in treated plants than in the untreated plants. This result was in accordance with the progression of disease in detached leaves where the symptoms appeared earlier in untreated plants. It is clearly evident that the applications of bioinoculants greatly improved the health status of som plants and also induced systemic resistance in the plant against the fungal pathogen of leaf blight.